Awareness of sports education students on the use of wearable technology in physical activities - Saifuddin, Hasan; Putri, Wahyu Setia Kuscahyaning; Walandari, Puput Novia; Firmansyah, Johan (Bima Loka: Journal of Physical Education, 2025)
This study aims to analyze the level of awareness, use, perception, and adoption factors of wearable technology among physical education students in supporting physical activity. The study used a descriptive quantitative approach through an online survey of 48 students with a 14-item questionnaire instrument covering aspects of knowledge, experience of use, motivation, perceived benefits, obstacles, and readiness to adopt the technology. The results showed that 62.5% of respondents had sufficient understanding of wearable technology, but only 14.6% actively used it, while 62.5% had never used it, indicating a gap between awareness and use. The most recognized wearable features include step counters, heart rate monitors, sleep trackers, activity reminders, and GPS tracking. Perceptions of the benefits of wearables tended to be positive, with 62.5% of respondents rating them as important or very important in sports activities, and 66.7% feeling motivated to be more physically active. In addition, 89.6% of respondents acknowledged that wearables help objectively monitor performance, and 72.9% supported their integration into physical education learning. However, technology adoption remains hampered by economic and accessibility factors, with 52.1% of respondents citing price as the primary barrier and 25% citing limited device availability. Despite this, 43.8% of respondents were willing to participate in training, and 52.1% expressed potential interest. These findings suggest that wearable technology has significant potential to increase physical activity awareness through real-time feedback and objective monitoring. However, implementation requires a comprehensive strategy that includes increasing access, training, and gradual curriculum integration.